2007
DOI: 10.1093/humrep/dem045
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic abnormalities in patients bearing complete AZFc deletion of Y chromosome

Abstract: In the absence of the AZFc region, the transient zygotene stage is extended, and chromosome condensation is reduced. The low level of limited asynapsis, the normal H2AX staining and the incomplete loss of germ cells at the pachytene checkpoint indicate that the AZFc region is not critical for meiotic recombination. We suggest that the pachytene phenotype develops secondarily to a primary defect that influences meiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Moreover, after PGS, the same patient had all six analyzed embryos diagnosed as chromosomally abnormal, and four of them displayed sex chromosome aneuploidies. Some studies have suggested that Y chromosome microdeletions lead to impairment of normal meiotic synapsis of autosomes, as well as of sex chromosomes (20)(21)(22). These observations could explain the results in this patient; however, more meiotic studies are necessary to determine whether Y chromosome microdeletions in the AZFc region can result in asynapsis and subsequent aneuploidy of autosomes.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Moreover, after PGS, the same patient had all six analyzed embryos diagnosed as chromosomally abnormal, and four of them displayed sex chromosome aneuploidies. Some studies have suggested that Y chromosome microdeletions lead to impairment of normal meiotic synapsis of autosomes, as well as of sex chromosomes (20)(21)(22). These observations could explain the results in this patient; however, more meiotic studies are necessary to determine whether Y chromosome microdeletions in the AZFc region can result in asynapsis and subsequent aneuploidy of autosomes.…”
mentioning
confidence: 65%
“…Further, Y chromosome microdeletions have recently been reported to affect meiotic synapsis of the XY bivalent, as well as autosomal bivalents (20)(21)(22).…”
mentioning
confidence: 99%
“…On Yq region of AZF microdeletions was directly related with the phase in which spermatogenesis was arrested. Microdeletions of each locus cause spermatogenic arrest at a particular stage because each candidate genes of AZF locus specified a different phase of spermatogenesis (Geoffroy-Siraudin et al, 2007). Testicular histology of Y chromosome microdeletions in azoospermia and oligozoospermia infertile male had shown variable phenotypes of spermatogenesis (Singh & Raman, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In premeiotic germ cells of azoospermic men with distinct AZF microdeletions, distortion of the X-Y pairing structure was observed with Y chromosomes containing AZFb [34] and AZFc microdeletions [35] , and earlier with overlapping AZFb-c deletions [36] . AZFb deletions seem to interfere with the initiation of meiotic recombination [34,36] , whereas Y chromosomes with AZFc deletions displayed an extended zygotene stage and reduced condensation at pachytene [35] . These data suggest that meiotic arrest, the major testicular pathology of infertile [126] .…”
Section: Impairment Of Dynamic Azoospermia Factor Chromosome Structurmentioning
confidence: 98%